A tale of two leeches: Toward the understanding of the evolution and development of behavioral neural circuits. Issue 6 (23rd November 2020) - Kuo, Dian‐Han; De‐Miguel, Francisco F.; Heath‐Heckman, Elizabeth A. C.; Szczupak, Lidia; Todd, Krista; Weisblat, David A.; Winchell, Christopher J.
Abstract: In the animal kingdom, behavioral traits encompass a broad spectrum of biological phenotypes that have critical roles in adaptive evolution, but an EvoDevo approach has not been broadly used to study behavior evolution. Here, we propose that, by integrating two leech model systems, each of which has already attained some success in its respective field, it is possible to take on behavioral traits with an EvoDevo approach. We first identify the developmental changes that may theoretically lead to behavioral evolution and explain why an EvoDevo study of behavior is challenging. Next, we discuss the pros and cons of the two leech model species, Hirudo, a classic model for invertebrate neurobiology, and Helobdella, an emerging model for clitellate developmental biology, as models for behavioral EvoDevo research. Given the limitations of each leech system, neither is particularly strong for behavioral EvoDevo. However, the two leech systems are complementary in their technical accessibilities, and they do exhibit some behavioral similarities and differences. By studying them in parallel and together with additional leech species such as Haementeria, it is possible to explore the different levels of behavioral development and evolution. Abstract : Research Highlights:   Behavior is a biological phenotype that can be studied by using an EvoDevo approach. Changes in the neural circuits can result in behavioral change. The leech Hirudo has been used to study neural circuits in the past half‐century. Helobdella has been used to study leech development. By comparing the different leeches, it is possible to characterize the molecular changes underlying changes in neural circuits and behavior. As a direct developer, the entire course of development is experimentally tractable in the leech. This would provide a unique opportunity to study the EvoDevo of behaviors.